2020
DOI: 10.34172/apb.2020.078
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alpha Mangostin on Epithelial-Mesenchymal Transition on Human Hepatocellular Carcinoma HepG2 Cells Surviving Sorafenib via TGF-β/Smad Pathways

Abstract: Purpose : This study was intended to find out the impact of alpha mangostin administration on the epithelial-mesenchymal transition (EMT) markers and TGF-β/Smad pathways in hepatocellular carcinoma Hep-G2 cells surviving sorafenib. Methods: Hepatocellular carcinoma HepG2 cells were treated with sorafenib 10 μM. Cells surviving sorafenib treatment (HepG2surv) were then treated vehicle, sorafenib, alpha mangostin, or combination of sorafenib and alpha mangostin. Afterward, cells were observed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…α-Man has exhibited anti-cancer effects in pancreatic cancer cells through repression of PI3K/Akt signaling pathways, 44) whereas in INS-1 cells, it significantly increases insulin secretion via activation of the PI3K/Akt pathways. 45) Similarly, α-man exerts opposite effects on TGF-β pathways in hepatic stellate cells and HepG2 cells. 29,46) These findings suggest that α-man function differently depending on the cell type.…”
Section: -Man Inhibited Fibrosis By Suppressing the Nox4-generated Ros In Cultured Cardiac Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…α-Man has exhibited anti-cancer effects in pancreatic cancer cells through repression of PI3K/Akt signaling pathways, 44) whereas in INS-1 cells, it significantly increases insulin secretion via activation of the PI3K/Akt pathways. 45) Similarly, α-man exerts opposite effects on TGF-β pathways in hepatic stellate cells and HepG2 cells. 29,46) These findings suggest that α-man function differently depending on the cell type.…”
Section: -Man Inhibited Fibrosis By Suppressing the Nox4-generated Ros In Cultured Cardiac Fibroblastsmentioning
confidence: 99%
“…45) Similarly, α-man exerts opposite effects on TGF-β pathways in hepatic stellate cells and HepG2 cells. 29,46) These findings suggest that α-man function differently depending on the cell type. Further studies are required to elucidate the mechanisms by which α-man regulates cardiac hypertrophy and fibrosis.…”
Section: -Man Inhibited Fibrosis By Suppressing the Nox4-generated Ros In Cultured Cardiac Fibroblastsmentioning
confidence: 99%
“…Additionally, a recent study has demonstrated the chemosensitizing effect of AM, leading to its use as adjunctive treatment to the available anticancer chemotherapeutic agent. Adenina et al (2020)…”
Section: Discussionmentioning
confidence: 99%
“…To select SOR-surviving cells, HepG2 was incubated with SOR 10 mM for 24 hours. Cells that survived 24-hour SOR 10 mM incubation were then considered SOR-surviving cells described by Adenina et al (2020). Afterward, the medium was changed, and the cells were treated 24 hours with DMSO or SOR 10, AM 20 mM, or a combination of SOR 10 and AM 20 mM.…”
Section: Cells and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation